2016
DOI: 10.1186/s12879-016-1590-3
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of outcomes of device-associated osteomyelitis treated with daptomycin

Abstract: BackgroundDaptomycin appears well tolerated and effective for osteomyelitis treatment. However, limited data exist regarding daptomycin use for treatment of device-associated osteomyelitis (DAO).MethodsWe used a retrospective, observational database (Cubicin® Outcomes Registry and Experience [CORE® 2007–2009]) that assessed patients treated with daptomycin to evaluate the characteristics of patients with DAO, outcomes after daptomycin treatment, and safety of daptomycin in this setting. Information from 54 ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Recent data on the treatment of bone and joint infections come largely from retrospective and/or observational studies such as TOUR. The retrospective, observational Cubicin ® Outcomes Registry and Experience (CORE ® ) study in the USA identified 82 patients with device-associated osteomyelitis treated with daptomycin, of whom 48 had available follow-up information; 22/27 (82%) of patients with prosthetic joint infection and 18/21 (86%) patients with other hardware-associated osteomyelitis had a cure or improvement with daptomycin treatment [27]. Patients with osteomyelitis and orthopedic device infections in a retrospective European registry (EU-CORESM) were cured or improved after daptomycin treatment in 522/638 (81.8%) cases [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data on the treatment of bone and joint infections come largely from retrospective and/or observational studies such as TOUR. The retrospective, observational Cubicin ® Outcomes Registry and Experience (CORE ® ) study in the USA identified 82 patients with device-associated osteomyelitis treated with daptomycin, of whom 48 had available follow-up information; 22/27 (82%) of patients with prosthetic joint infection and 18/21 (86%) patients with other hardware-associated osteomyelitis had a cure or improvement with daptomycin treatment [27]. Patients with osteomyelitis and orthopedic device infections in a retrospective European registry (EU-CORESM) were cured or improved after daptomycin treatment in 522/638 (81.8%) cases [28].…”
Section: Discussionmentioning
confidence: 99%
“…Taking these limitations into account, our work nonetheless demonstrates that combining fusidic acid with linezolid or daptomycin could be a useful therapeutic option against staphylococcal biofilm-related infections in areas and/or situations where resistance to these drugs is low (essentially, in North America [19][20][21], but not in Europe [50,51] or other regions of the world [52,53]). Linezolid and daptomycin, although recommended for short-term use, sometimes need to be use for long periods of time (Ͼ3 weeks [54][55][56][57]) in difficult situations, such as those involving biofilms, which may expose the patients to higher risks of adverse events. Synergic combinations, as those evidenced here with fusidic acid, may offer a real opportunity in this context.…”
Section: Discussionmentioning
confidence: 99%
“…This project compared vancomycin powder to both daptomycin and rifampin powders. Daptomycin, a cyclic lipopeptide, maintains in vitro efficacy against most clinically relevant gram‐positive pathogens and is effective in patients with prosthetic joint or other orthopedic device infections when delivered systemically . This study, however, concluded that there is a lack of bacteria reduction when vancomycin or daptomycin powder was solely placed directly into the wound of a mature biofilm model.…”
Section: Discussionmentioning
confidence: 92%